Modified Iron Deposition in Nigrosomes by Pharmacotherapy for the Management of Parkinson’s Disease - Wang, Mengdi; Wang, Hongxia; Wang, Jing; Lu, Shujun; Li, Chen; Zhong, Xiaofei; Wang, Nan; Ge, Ruli; Zheng, Qi; Chen, Jinbo; Wang, Hongcai (Frontiers in Molecular Biosciences, 2022)
Background Increased iron deposition in the nigrosome as assessed by susceptibility-weighted imaging (SWI) is involved in the pathogenesis of Parkinson’s disease (PD). This study investigated the effects of antiparkinson drugs on iron deposition in the nigrosome of PD patients. Methods Based on the retrospective analysis of clinical data, alterations in iron deposition in the substantia nigra was investigated in 51 PD patients across different types of therapy and in 9 Parkinson-plus syndrome patients. The Movement Disorder Society revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part-Ⅲ/-Ⅳ (UPDRS Ⅲ/Ⅳ) was utilized to evaluate motor function and complications. SWI (slice=0.6 mm) was used to detect iron deposition in the nigrosome and substantia nigra. Nigrosome loss was scored on a 1-point nigrosome visibility scale. Visual assessment of dorsolateral nigral hyperintensity (DNH) was separately performed for each side of the nigrosome with SWI. Results Increased UPDRS Ⅲ scores were correlated with low nigrosome scores based on correlation analysis at a disease duration of 6-12 months(r=-0.8420). The loss of nigrosome on SWI were clearly inhibited in PD patients with a 3-5-year duration of administration of antiparkinson medications compared with no treatment. Decreased UPDRS Ⅲ scores and increased nigrosome scores were observed in the regular treatment of PD patients with a 6-7-year disease duration. For patients with Parkinson-plus syndromes such as multiple system atrophy (MSA), iron accumulation was apparent in the corpus striatum and substantia nigra compared with patients with progressive supranuclear palsy (PSP). Conclusions Thus, early and regular treatment with antiparkinson drugs not only alleviates the chance of PD disability but also prevents the loss of DNH, namely, iron accumulation in the nigrosome.